Developing a new justification for assent. Issue 1 (December 2016) - Sibley, Amanda; Pollard, Andrew; Fitzpatrick, Raymond; Sheehan, Mark
Abstract Background Current guidelines do not clearly outline when assent should be attained from paediatric research participants, nor do they detail the necessary elements of the assent process. This stems from the fact that the fundamental justification behind the concept of assent is misunderstood. In this paper, we critically assess three widespread ethical arguments used for assent: children's rights, the best interests of the child, and respect for a child's developing autonomy. We then outline a newly-developed two-fold justification for the assent process: respect for the parent's pedagogical role in teaching their child to become an autonomous being and respect for the child's moral worth. Discussion We argue that the ethical grounding for the involvement of young children in medical decision-making does not stem from children's rights, the principle of best interests, or respect for developing autonomy. An alternative strategy is to examine the original motivation to engage with the child. In paediatric settings there are two obligations on the researcher: an obligation to the parents who are responsible for determining when and under what circumstances the child develops his capacity for autonomy and reasoning, and an obligation to the child himself. There is an important distinction between respecting a decision and encouraging a decision. This paper illustrates that the process of assent is an important way in which respect for the child as an individual can be demonstrated, however, the value lies not in the child's response but the fact that his views were solicited in the first place. Summary This paper demonstrates that the common justifications for the process of assent are incomplete. Assent should be understood as playing a pedagogical role for the child, helping to teach him how specific decisions are made and therefore helping him to become a better decision-maker. How the researcher engages with the child supports his obligation to the child's parents, yet why the researcher engages with the child stems from the child's moral worth. Treating a child as having moral worth need not mean doing what they say but it may mean listening, considering, engaging or involving them in the decision.